Pengembangan Media Komik untuk Meningkatkan Pemahaman Kesadaran Budaya Kelas IV Sekolah Dasar - rohatul, meisyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning tool to improve the cultural awareness of fourth-grade elementary school students. The background of this study is the low level of understanding of local cultural diversity, especially in the era of globalization, where the younger generation must have a positive and open attitude towards culture. This study uses a research and development (R&D) method with a modified Borg and Gall model in the following stages: (1) preliminary research, (2) planning, (3) initial product development, (4) limited testing, (5) product modification, and (6) field testing. The research subjects were 40 fourth-grade students at SDN Wanajaya 04 Elementary School in Bekasi Regency. Data collection instruments included interviews, observations, questionnaires, and comprehension tests. Data analysis was conducted using descriptive quantitative and qualitative methods. The results showed that the Dodo Cinta Budaya comic media met the feasibility criteria of subject matter experts (97%), media experts (96%), and student responses (100%) with a category of highly feasible. The effectiveness test showed a significant increase in students' cultural awareness comprehension scores. This comic book is expected to be an alternative in IPAS and Multicultural Education learning in elementary schools.